As centralidades em Marabá-PA: análise dos rearranjos a partir dos supermercados - Carvalho, Magno Ricardo Silva de (2020)
This research analyzed the city of Marabá, an urban area located in the Eastern Amazon, in the southeast of the State of Pará. The objective of the study was to understand the centralities in the intra-urban space of the city, with regard to trade, its dynamics and changes in recent years, in view of the implementation of new consumption spaces, primarily a hypermarket and some supermarkets. For its development, we start from an analysis about the changes in the supermarket sector, as well as, of the relationships of these transformations with different agents, above all, the citizens. The methodological path carried out consisted of a literature review on themes and processes selected for analysis and which are directly related to the studied urban-spatial phenomenon. In this case, the bibliographic research was carried out, among others, using the following terms: center (s) and centrality (s), structure, structuring of the city, medium city, spatial strategies of business groups and the relationship between the implantation and performance of large commercial areas with urban spaces, especially in intermediate cities. We dedicate ourselves to reading the selected material, as well as to documents such as the Revision of the Participatory Master Plan of municipality. In addition to this step, we resorted to conducting interviews with representatives of the enterprises and applying questionnaires with local consumers. The survey of primary data through forms applied at the exits of supermarkets aimed to understand people's spatial practices, as well as the reach of these stores. We also use cartographic and photographic resources in order to better understand the spatial transformations. Thus, we can affirm that there were significant changes in the centralities and, consequently, in the structuring of the city. We can consider a conformation of new polar and linear centralities and a multi (poly) centrality, processes in which the installation of large projects was of paramount importance.